ENGLISH CONTENT CREATOR TRAINING FOR TOUR GUIDES AT KEBUMEN ENGLISH TOURISM VILLAGE (KWIK) AS A MEANS TO OVERCOME ANXIETY IN GUIDING TOURS IN ENGLISH - Nugraha, Novanda Alim Setya; Chaeruman, Uwes Anis; Lustyantie, Ninuk (Universitas PGRI Palembang, 2025)
Anxiety is one of the affective factors that influences foreign language learning, particularly in speaking. Anxiety appears to be an important factor in language learning progress, as it has a hindering effect on learners' oral performance. One approach to addressing this issue is through